DESIGNING TEXTILE WASTE SHREDDER MACHINE FOR CONTINOUS PRODUCT - Afifuddin, Mokh; Harianto, Dedy; Sugiyarto, Sugiyarto; Eddy, Yulius Sarjono; Yulianto, Bambang; Darmawi, Ahmad (Center for Study and Journal Management FTI UMI, 2021)
The textile and textile products industry is one of the mainstay commodities of the manufacturing industry as well as a driving force for national economic development. Like any production process, the textile manufacturing process also produces waste or residual substances called textile waste. Likewise the impact of the activities of garment, tailor, fashion, apparel and convection, one of which is patchwork waste. If the patchwork waste is not handled properly, it will result in waste generation which will have an impact on pollution in the environment. Lack of tools that can treat textile waste, resulting in less optimal handling of textile waste. This research is trying to make a design of a cloth chopping machine that is used to crush the remains of large rags into small pieces of cloth. Thus the packaging of fabric waste is easier and more efficient, besides that it can also be used as raw material for other products so that it can reduce fabric waste that pollutes the environment. In developing the model and design of a textile waste chopping machine, this chopping machine will cut the patchwork which can be sized according to your wishes. It is hoped that the results of this research will contribute to the development, advancement and appropriate technology. The design of this textile fabric waste chopper will provide a practical solution and zero waste process in a textile and garment industry.